2020
DOI: 10.1038/s41597-020-00613-z
|View full text |Cite
|
Sign up to set email alerts
|

Seventy-year long record of monthly water balance estimates for Earth’s largest lake system

Abstract: We develop new estimates of monthly water balance components from 1950 to 2019 for the Laurentian Great Lakes, the largest surface freshwater system on Earth. For each of the Great Lakes, lake storage changes and water balance components were estimated using the Large Lakes Statistical Water Balance Model (L2SWBM). Multiple independent data sources, contributed by a binational community of research scientists and practitioners, were assimilated into the L2SWBM to infer feasible values of water balance componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…We showed that peak monthly E occurred mostly from August to October at Lake Erie and the winter months (October–March) accounted for near 30% of annual E . Such seasonality of E is distinct from other Great Lakes, which showed peak monthly E in December–January and that the majority of annual E was contributed during the winter months (Cleave et al, 2014; Do et al, 2020; Lofgren & Zhu, 2000; Moukomla & Blanken, 2017). The unique seasonality of E over Lake Erie likely is due to its bathymetry, latitude, and climate (Table 6).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…We showed that peak monthly E occurred mostly from August to October at Lake Erie and the winter months (October–March) accounted for near 30% of annual E . Such seasonality of E is distinct from other Great Lakes, which showed peak monthly E in December–January and that the majority of annual E was contributed during the winter months (Cleave et al, 2014; Do et al, 2020; Lofgren & Zhu, 2000; Moukomla & Blanken, 2017). The unique seasonality of E over Lake Erie likely is due to its bathymetry, latitude, and climate (Table 6).…”
Section: Discussionmentioning
confidence: 74%
“…Our study provided the first direct and multiyear measurements of E over western Lake Erie, with annual E of 635 ± 42 mm and 604 ± 32 mm at the nearshore (CB) and offshore (LI) sites, respectively. Previous studies based on modeling and indirect approaches (e.g., energy budget, water balance, and mass transfer) reported a wide range of annual E over Lake Erie, on the order of 500–1,000 mm (Derecki, 1976; Do et al, 2020; Gronewold et al, 2019; Lofgren & Zhu, 2000; Moukomla & Blanken, 2017; Neff & Nicholas, 2005). We advocate that the E estimates need to be better constrained, especially those based on indirect approaches that often substantially overestimate E over Lake Erie (e.g., 898–903 mm) (Derecki, 1976; Neff & Nicholas, 2005; Schertzer, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data sets and model simulations for this project derived from the GLM-HMD (Hunter et al, 2015), L2S-WBM (Do et al, 2020;Gronewold et al, 2020), WCPS (Deacu et al, 2012;Durnford et al, 2018), AHPS (Apps et al, 2020;Gronewold et al, 2011), WATFLOOD (Kouwen, 1988), CaPA (Lespinas et al, 2015;Mahfouf et al, 2007), MPE (Seo, 1998;Seo & Breidenbach, 2002), and the "Merged" overlake precipitation data set (Gronewold et al, 2018) have been compiled and sotred on the University of Michigan Deep Blue archive at https://deepblue.lib.umich.edu/data/concern/data_sets/sb3978457.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…We then aggregated these estimates, using the surface area of each lake, into a single value of total overlake precipitation, total overlake evaporation, and total lake inflow through tributary runoff. Details of our parameterization of the L2SWBM for this study, as well as the L2SWBM simulations and corresponding code, are available via the University of Michigan's Deep Blue archive (Do et al., 2020).…”
Section: Data Setsmentioning
confidence: 99%